Edukasi Gaya Hidup Sehat untuk Mencegah Hipertensi Dini pada Remaja di SMA Negeri 3 Indrapuri - Ellyza Fazlylawati; Muhammad Reza Rizki; Nurul Amna; Muis Muis; Muliya Sari; Fajri Fajri; Arza Rufli; Andi Mulyadi; Nabella Nabella (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Hypertension is no longer limited to adults; it is also increasingly common among adolescents due to unhealthy lifestyle changes, such as poor dietary habits, lack of physical activity, and the habit of staying up late. This condition has the potential to increase the risk of cardiovascular disease during their productive years if preventive measures are not taken early on. Therefore, ongoing health education is needed to raise awareness among adolescents about adopting healthy lifestyle behaviors. The objective of this activity was to provide health education to improve adolescents’ knowledge, attitudes, and awareness regarding the importance of adopting a healthy lifestyle as a means of preventing early-onset hypertension. The methods used in this community service activity were lectures and question-and-answer sessions. The results of the activity showed an increase in understanding and knowledge about healthy lifestyles to prevent early-onset hypertension among adolescents at Indra Puri State High School 3. Participants were also enthusiastic and cooperative throughout the activity and actively participated in the discussion sessions. It is hoped that high school students will consistently adopt a healthy lifestyle to prevent early-onset hypertension and improve their health in the future.